Entrée dans la vie adulte d’anciens placés en village d’enfants : Fin des prises en charge et parcours d’accès à l’autonomie - Annick-Camille Dumaret; Pascale Donati; Monique Crost (Sociétés et Jeunesses en Difficulté, 2010)
This study explores the period of leaving care from a SOS children’s village and the transition to independent living of 123 people currently aged 23 to 50. The approximately thirty year period following their discharge from care allowed to examine the principal changes both in care practices and in the conditions to access to independence and autonomy of these adults from two generational groups, those younger than 35 years of age and the others. The youngest generations of ex-care subjects benefited from more institutional support during and after the placement, but faced more difficulties entering the workforce. The large majority underwent transitions by the age of 24-25, free of major problems. Access to residential and material independence was associated to diplomas and mental health. A qualitative approach analyzed their representations of the transition period and their pathways to autonomy, according to gender and generational groups. These adults reported high level of perceived support from their siblings and their foster caregivers, besides the institutional support. The social integration processes of these care leavers ranged from chaotic to gradual. Difficulties they had to face when leaving care would have undoubtedly been more common and more severe if the placement had been shorter and less stable. For all these young people, prolonging social worker support beyond 21 years of age proved to be essential but must also be further developed to help them personally and academically in order to make successful transitions to adulthood.